Understanding How Management Students Choose their Career - Raja Khwarizmi; Tsabita Khwarazmita (Universitas Muhammadiyah Malang, 2022)
Career research is still a topic that is not widely discussed, especially among undergraduates and alumni. Even though this still needs to be explored more deeply considering that a career is part of the responsibility of many parties in their selection. This study seeks to explore career choices by students by uniting family influence, personal interest, and economic conditions. The aim is to find out more clearly the variables that can influence the career choices of undergraduates at public and private universities. The population and samples respectively amounted to 970 and 95 respondents who could be used in the study. The use of sampling technique is using accidental sampling and the data is processed using SmartPLS 4.0. The findings were surprising in this study where family influence has an effect on career choice. On the other hand, personal interest and economic conditions have no effect on career choice.